Treatment of palm oil mill effluent using microorganisms - Abdul Karim, Mohamed Ismail; Daud, Nurul Aima; Alam, Md. Zahangir (IIUM Press, 2011)
Palm oil mill effluent (POME) is produced in large volumes by many of the palm oil mills in Malaysia and poses a major source of pollution. POME contains large quantities of organic matter in the form of total solids that contribute to high biological oxygen demand (BOD) and chemical oxygen demand (COD) in wastewater if left untreated. A study was conducted to evaluate the potential use of Trichoderma harzianum and the mix culture of Trichoderma harzianum and Penicillium for the treatment of POME in reducing the pollutant. Using central composite design (CCD) experiment, each flask containmg 100 ml POME is treated with an inoculums consisting of 3% inoculums containing 3 x 108 spores/ml and fermented in shake flask with pH 3,6,9 and the agitation speed; 50, 150,250 rpm and incubated at 30°C for 5 days. Sample of the POME were analyzed at 24 intervals for BOD, COD and total suspended solids (TS).The result showed that the mix culture of Trichoderma harzianum and Penicillium gave better reduction of COD, and TSS with a value of 87.5% and 28.9%, respectively as compared to Trichoderma harzianum in which the value for reduction of COD and TSS is 85.2% and 27.2%, respectively at day 5 of the treatment.